Bis(diisopropylammonium) thiosulfate and bis(tert‐butylammonium) thiosulfate. (5th February 2013) - Okuniewski, Andrzej; Chojnacki, Jaroslaw; Baranowska, Katarzyna; Becker, Barbara
Abstract : Two new dialkylammonium thiosulfates, namely bis(diisopropylammonium) thiosulfate, 2C6 H16 N + ·S2 O3 2−, (I), and bis( tert ‐butylammonium) thiosulfate, 2C4 H12 N + ·S2 O3 2−, (II), have been characterized. The secondary ammonium salt (I) crystallizes with Z = 4, while the primary ammonium salt (II), with more hydrogen‐bond donors, crystallizes with Z = 8 and a noncrystallographic centre of inversion. In both salts, the organic cations and thiosulfate anions are linked within extensive N—H...O and N—H...S hydrogen‐bond networks, forming extended two‐dimensional layers. Layers are parallel to (10 ) in (I) and to (002) in (II), and have a polar interior and a nonpolar hydrocarbon exterior. The layered structure and hydrogen‐bond motifs observed in (I) and (II) are similar to those in related ammonium sulfates.